Effect of School Welfare on English Teachers’ Job Satisfaction in the Selected Secondary Schools in Kabale Municipality. - Katwesigye, Kevin (Kabale University, 2024)
The research investigated how school welfare impacts the job satisfaction of English teachers in selected secondary schools in Kabale Municipality. The study aimed to determine the influence of housing, provision of meals, and access to medical care on English teachers' job satisfaction. A cross-sectional survey methodology was employed, using questionnaires and interviews for data collection. Regarding the effect of housing on job satisfaction, the findings indicated that adequate and affordable housing significantly contributes to the overall well-being of English teachers, thereby enhancing job satisfaction. Proximity of housing to the school also positively affects job satisfaction by allowing teachers more time to prepare lesson plans and teach effectively.